State of the world 2013 : is sustainability still possible? - Starke, Linda, (Island Press, 2013)
"In 'State of the World 2013: Is Sustainability Still Possible?', experts define clear sustainability metrics and examine various policies and perspectives, including geoengineering, corporate transformation, and changes in agricultural policy, that could put us on the path to prosperity without diminishing the well-being of future generations. If these approaches fall short, the final chapters explore ways to prepare for drastic environmental change and resource depletion, such as strengthening democracy and societal resilience, protecting cultural heritage, and dealing with increased conflict and migration flows."--Provided by publisher.